(untitled) (Boca Raton, 2012)
Completely revised and updated, this second edition includes new sections on fermented seafood such as fish sauce, updated U.S. standards, and permitted food ingredients derived from each fermented product. An international panel of experts from government, industry, and academia provide an in-depth review of fermentation history, microorganisms, quality assurance practices, and manufacturing guidelines
Keywords: Animal products,Thực phẩm lên men,Sản phẩm động vật,Fermented foods